A novel ontological approach to semantic interoperability between legacy air defence command and control systems. (26th October 2011) - Partridge, Chris; Lambert, Mike; Loneragan, Mike; Mitchell, Andrew; Garbacz, Pawel
In common with many other government defence departments, the UK Ministry of Defence (MoD) has realised that it has a plethora of legacy systems that were procured as domain specific with little emphasis given to integration requirements. In particular, it realised that the lack of integration between a significant number of the legacy air defence command and control (AD-C2) systems meant it could not deliver the increased agility needed for joint force AD and that current approaches to integration were unlikely to resolve the problem. They realised that they needed a new approach that demonstrably worked. This paper describes a programme initiated by the MoD to address this problem through the formulation of a novel solution and its demonstration in the tactical AD-C2 environment using a sample of these existing legacy systems. It describes the ontological solution deployed to resolve the 'hard' semantic interoperability challenge. It outlines the physical and semantic architecture that was developed to support this approach and describes the implemented planning and collaborative execution (PACE-based) and semantic interoperability engine (SIE) solution.